PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE BAMBOO DANCING UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP SISWA SEKOLAH DASAR - Juita Gusniati; Yenni Fitra Surya; Mufarizuddin; Muhammad Syahrul Rizal; Iis Aprinawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low conceptual understanding abilities of fourth-grade students at UPT SDN 005 Bukit Ranah in the IPAS (Integrated Science and Social Studies) subject. The learning process, which was still teacher-centered and lacked methodological variation, caused students to struggle in interpreting, exemplifying, classifying, summarizing, concluding, comparing, and explaining the learning concepts. This study aimed to improve students' conceptual understanding through the implementation of the cooperative learning model Bamboo Dancing. This study employed Classroom Action Research (CAR) conducted in two cycles. The subjects were 16 fourth-grade students at UPT SDN 005 Bukit Ranah. Data collection techniques included observation, tests, and documentation. The research instruments used were observation sheets for teacher and student activities, and conceptual understanding tests. The data analysis techniques included both qualitative and quantitative analysis. results showed an improvement in students’ conceptual understanding. In the pre-action stage, the average score was 62.80 with a mastery level of 31%. After the first cycle, the average score increased to 73.44 with a mastery level of 62.5%. In the second cycle, the average score further increased to 85.63 with a mastery level of 87.5%. This improvement indicates that the Bamboo Dancing cooperative learning model is effective in enhancing students' conceptual understanding. It is concluded that the implementation of the Bamboo Dancing cooperative learning model can improve students’ conceptual understanding in the IPAS subject for fourth-grade students at UPT SDN 005 Bukit Ranah.